Pengaruh Media Animasi Terhadap Praktik Cuci Tangan Pakai Sabun Pada Anak di SDN Banguntapan - Aulia Devi Septiyani; Khristina Dias Utami; Retno Sumiyarini (Jurnal Indonesia Sehat, 2023)
Background: In 2018, the category of children aged 10 years or above in Indonesia had a prevalence of hand washing with soap of 49.80%. Meanwhile, in the Special Region of Yogyakarta,  it reached 52.3%, and the Bantul regency had a percentage of 46.2%. Hand washing with soap is an essential basic technique to prevent the spreading of infectious diseases. School-age children are targeted in this education because they are vulnerable to infectious diseases. Education using animated media is carried out as an effort to prevent disease and form clean and healthy lifestyle habits in children at the same time. Objective: This research aims to find out the effect of animated media on the practice of hand washing with soap in children at SDN (Public Elementary School) Banguntapan. Methodology: This quantitative research employed a pre-experimental design using the One Group Pre-Test- Post-Test approach. The sample in this research were the students of grades 1-6 totaling 65 students selected using a stratified random sampling technique. The practice of hand washing with soap was measured using an observation sheet filled out by the researcher and research assistant before and after the education using animated media. Results: The results show a difference between pretest and posttest. The pretest results show that a small number of the respondents before given the animated media were included in the unskilled category as many as 25 respondents (38.5%).  After being given the animated media, there are as many as 65 respondents (100%) who are in the skilled category with the practice of washing hands with soap. The data analysis used the McNemar test showing the result of p 0.000 (p <0.05). Conclusion: There is an effect on the practice of hand washing with soap in children before and after the education using animated media is given.